If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(7x-4)+9=5(x+3)-17
We move all terms to the left:
-2(7x-4)+9-(5(x+3)-17)=0
We multiply parentheses
-14x-(5(x+3)-17)+8+9=0
We calculate terms in parentheses: -(5(x+3)-17), so:We add all the numbers together, and all the variables
5(x+3)-17
We multiply parentheses
5x+15-17
We add all the numbers together, and all the variables
5x-2
Back to the equation:
-(5x-2)
-14x-(5x-2)+17=0
We get rid of parentheses
-14x-5x+2+17=0
We add all the numbers together, and all the variables
-19x+19=0
We move all terms containing x to the left, all other terms to the right
-19x=-19
x=-19/-19
x=1
| 55=-y+263 | | -(5x-12)+3=9x-2-10x | | 88=4(4-3m) | | 2x-3(x+1)=8x-9+x | | 9(-2x-1)-x=25+4(x+3) | | -7x-4x+1=6(x-14) | | 2(4+8k)=5k+19 | | 3(x-2)+4=2(x-1)+5 | | 11-5(3x+2)=-9(x-1)+16 | | 4(x+2)-2(2(x-5)=30 | | 7(-4-8v)-4=-6(-4v-8) | | 0.5(6x-14)=5x-8+2x | | -4(x-7)+5=1-(2x+6) | | 2x+5+3x+10=−40 | | 3(5n-1)+8=-2(-6n-5)=3n-5 | | 2+4x-x=-8x+6+15x | | -4b+34=4(-b=8)-2 | | -(r+5)=-13+3r | | 42+5t=84 | | 2+u/5=-23 | | 15-2z=12-2z | | 7k-4k-11=5k=3-6 | | 11x+7+3=65 | | 10=k8 | | 479+f=563 | | 140=5(4=4a) | | 2b+6-4b=-6 | | -37=12c+41 | | 15,936+f=19,579 | | 14=q−–6 | | 17x-6=14x+3 | | 2e+17=5e+50 |